QCD thermodynamics using five-dimensional gravity - Megías Fernández, Eugenio; Pirner, Hans J.; Veschgini, Kambis (Physical review. D, Particles, fields, gravitation, and cosmology, 2011)
We calculate the critical temperature and free energy of the gluon plasma using the dilaton potential [B. Galow, E. Megias, J. Nian, and H. J. Pirner, Nucl. Phys. B834, 330 (2010).] in the gravity theory of anti-de Sitter/QCD. The finite temperature observables are calculated in two ways: first, from the Page-Hawking computation of the free energy, and secondly using the Bekenstein-Hawking proportionality of the entropy with the area of the horizon. Renormalization is well defined, because the T=0 theory has asymptotic freedom. We further investigate the change of the critical temperature with the number of flavors induced by the change of the running coupling constant in the quenched theory. The finite temperature behavior of the speed of sound, spatial string tension and vacuum expectation value of the Polyakov loop follow from the corresponding string theory in AdS5.
Gesehen am 16.08.2022